Capital gains tax in South Africa - Carlson, Mark Kenneth (Department of Public Law, 2026)
Albert Einstein once said that the "hardest thing in the world to understand is the income tax"'. It is thus most appropriate that Capital Gains Tax ("CGT") has not been introduced into South African law as a separate tax but has rather been added to the Income Tax Act 58 of 1962 ("the Act") by means of an Eighth Schedule ("the Schedule"), with the effect that the levying, collection and administration of CGT al I take place in terms of the Act. The detail of much of the South African version of CGT is difficult to come to grips with, as many of the provisions of the Schedule are lengthy and complex, and some of the key definitions and concepts are extremely technical. A further problem with understanding CGT is that while the legislation pertaining thereto was introduced by the Taxation Laws Amendment Act 5 of 200 I, such legislation was shortly thereafter amended by the Revenue Laws Amendment Act 19 of 2001 and further proposed amendments have already been gazetted in the form of the Second Revenue Laws Amendment Bill, no. 84 of 2001. It is thus apparent that the authorities intend regularly amending the CGT legislation in until it 'settles down'.